Early Life Health Interventions and Childhood Development: Evidence from Special Care Nursery Assignment in Australia's Northern Territory - Kevin T. Schnepel; Stefanie Schurer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
This paper studies the effect of improved early-life health care, through assignment to a special care nursery (SCN), on childhood development and school achievement. We use linked administrative data in the Northern Territory of Australia and exploit the fact that assignment to SCN is largely based on rules of thumb involving low birth weight thresholds. We find large positive effects of SCN assignment on development at age five and some persistent improvements in test scores. Our results suggest that costly early-life health interventions, that are shown to increase survival probabilities of children in the short run, can also substantially boost cognitive and non-cognitive skills.
Keywords: J13; I14; I18; I24; 330; Early-life health treatments; special care nurseries; school achievements; noncognitive skills; school readiness